Strategi Komunikasi Komisi Penanggulangan AIDS (KPA) Provinsi Kalimantan Tengah dalam Menyosialisasikan Penanggulangan HIV dan AIDS di Kalimantan Tengah - srie rosmilawati; Lisnawati Lisnawati (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
The main problem in this study is the increase in the number of people in Central Kalimantan who are infected with the HIV and AIDS virus from year to year. Given these problems, the researchers were interested to find out how the communication strategy of the Central Kalimantan AIDS Control Commission (KPA) in Socializing HIV and AIDS prevention, with a research locus in Central Kalimantan Province. The theory used in this study is the Theory of Effective Communication Strategies (Arifin), namely the determination of communication strategies based on steps to get to know the audience, compose messages, set methods, and media selection. This study uses a qualitative approach with in-depth interview data collection techniques, observation, and also documentation. The research subjects were KPA officers in Central Kalimantan Province and also the people of Central Kalimantan. The focus of the research lies in the communication strategy undertaken by the KPA of Central Kalimantan Province in socializing HIV and AIDS prevention to the community. The results of the study showed that up to now the KPA of Central Kalimantan Province had been quite good and effective in developing a communication strategy used in the process of socializing HIV and AIDS prevention to the people of Central Kalimantan. Whereas indicators for getting to know the public are still ineffective because the KPA of Central Kalimantan does not make an introduction to the audience itself, and only refers to government programs.